1999
DOI: 10.1210/jcem.84.7.5826
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hepatocyte Growth Factor in Patients with Peripheral Arterial Occlusive Disease

Abstract: Hepatocyte growth factor (HGF) is a multifunctional protein implicated in tissue regeneration, wound healing, and angiogenesis. We measured serum HGF concentrations in 37 patients with peripheral arterial occlusive disease (PAOD). Among them, 36 patients underwent arteriography. Serum HGF concentrations were also measured in 40 control subjects who remained free of vascular, liver, kidney, or lung disease. Patients with PAOD showed elevated serum HGF concentrations compared with control subjects (0.40+/-0.02 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
(29 reference statements)
0
20
1
Order By: Relevance
“…Although the present study demonstrated no increase in serum HGF concentration during gene therapy, the circulating level of HGF is elevated in patients with hypertension, PAD, and myocardial infarction. [31][32][33] There was no evidence of edema in the patients transfected with the human HGF gene, in marked contrast to a phase I/IIa VEGF trial in which 60% of patients developed moderate or severe edema. The difference between HGF and VEGF might be mediated by different actions on the migration of vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 72%
“…Although the present study demonstrated no increase in serum HGF concentration during gene therapy, the circulating level of HGF is elevated in patients with hypertension, PAD, and myocardial infarction. [31][32][33] There was no evidence of edema in the patients transfected with the human HGF gene, in marked contrast to a phase I/IIa VEGF trial in which 60% of patients developed moderate or severe edema. The difference between HGF and VEGF might be mediated by different actions on the migration of vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 72%
“…28 Elevated HGF concentrations are found in hypertensive individuals with target-organ damage, 11 in diabetics 29 and in patients with coronary and peripheral arterial disease. 30,12 A positive association between plasma HGF concentrations and carotid arterial atherosclerosis and dilation has also been reported. 31 HGF has recently been reported to be elevated in obese subjects, 15 however, the population studied was more markedly obese (mean BMI ¼ 48 kg/m 2 ) compared to our obese population (mean BMIB39 kg/m 2 ).…”
Section: 4mentioning
confidence: 89%
“…For example, both HGF and VEGF are expressed in adipose tissue and both of these have been implicated in pathogenesis of cardiovascular disease. [11][12][13] In addition to effects on endothelial cells in capillary beds many of the same factors are important in lymphangiogenesis and may therefore have a role in the development of cancer metastasis. While VEGF 14 and HGF 15 have been reported to be elevated in obese patients there are very few data on other angiogenic and antiangiogenic factors in obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Serum HGF was also significantly associated with blood pressure and severity of hypertension (1,15,21). However, the relation between SBP or diabetes mellitus and serum HGF is equivocal (6,7,16). For example, Nakamura et al (6) showed that serum HGF concentration in diabetes mellitus patients without hypertension was significantly lower than in normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that HGF might play an important role as a member of endothelium-specific growth factors locally released to counteract endothelial cell dysfunction (4). HGF level might be elevated in response to hypertension, acute myocardial infarction (5), diabetes mellitus with hypertensive complications (6) and peripheral arterial occlusive diseases (7). These findings suggest that serum HGF could be used as a diagnostic marker related to the progression of clinically overt atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%